Teacher as a creator of conditions for a child’s research activity in “Tablit” – an Innovative Kindergarten Curriclum - Marczewska, Maria (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
In her work the author focuses on the presentation of the experiences of preschool education teachers who have implemented an Innovative Kindergarten Curriculum “Tablit” (funded by the European Union). One of the main assumptions of the program is to rely on the project method while working with children in kindergarten. This method places a great emphasis on the development of the child’s research activity, independent as well as guided. Teachers designing daily activities in the kindergarten are trying to incorporate many elements of research, experimentation and exploring the world in a direct way. In addition, they face the challenge of organizing space and conditions for an independent research activity of the child. This article presents the experiences and reflections gained during the implementation of various projects. The author also tries to present different attitudes of teachers towards their new situation.